Communication with physicians and family about breast Cancer recurrence - Kimberly M. Kelly; Pragya Rai; Jamie L. Studts; Stephanie Dickinson; Beate Henschel; Mark Dignan; Mara Chambers; Hannah Hazard-Jenkins (Elsevier, 2023)
Objective: Adequate physician-patient communication about cancer recurrence is vital to quality of life and to informed decision-making related to survivorship care. The current study was guided by a cognitive-affective framework to examine communication with family and physicians about breast cancer recurrence risk. Methods: A survey of recently-diagnosed, early-stage breast cancer patients in Appalachia investigated physician-patient and familial communication about breast cancer recurrence risk. Results: Over 30% of participants reported not talking to family or physicians about breast cancer recurrence risk. Younger patients reported more conversations, and speaking with physicians was associated with greater perception risk factors associated with recurrence risk. Greater worry about recurrence was associated with more communication with family and plans to talk to family, physicians, and friends about recurrence risk in the future. Conclusion: Additional supports for patients and physicians are needed to improve understanding of breast cancer recurrence risk and risk factors for recurrence. Innovation: Family communication about breast cancer recurrence risk is understudied. The combination of physician and family communication adds novelty to our analysis.